ОБРАЗ ГЕРОЯ У ТВОРЧОСТІ М. СТЕЛЬМАХА ТА ЙОГО ТРАКТУВАННЯ УШКІЛЬНИХ ПІДРУЧНИКАХ 1960–1990-Х РОКІВ - Йовенко, Лариса (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті зроблено спробу розглянути образ героя-комуніста у романі «Кров людська – не водиця» М. Стельмаха та здійснити розгляд його інтерпретації в шкільних підручниках 1960–1990-х років. Визначено взаємозв’язки суспільного та художнього ідеалу окресленої епохи. На основі аналізу роману «Кров людська – не водиця», а також праць сучасних літературознавців розкрито поєднання в позитивному герої рис українського менталітету і комуністичних принципів. Встановлено спорідненість Свирида Мірошниченка з Давидом Мотузкою з роману «Бур’ян» А. Головка. В статье рассматривается образ героя-коммуниста в романе «Кровь людская – не водица» М. Стельмаха и интерпретация его в школьных учебниках 1960–1990-х годов. Определены взаимосвязи общественного и художественного идеала очерченной эпохи. На основе анализа романа «Кровь людская – не водица», а также работ современных литературоведов раскрывается сочетание в положительном герое черты украинского менталитета и коммунистических принципов. Установлено сходство Свирида Мирошниченко с Давидом Мотузкой из романа «Бурьян» А. Головко. This article at tempts to examine the image of communist hero in the novel «Blood of Man – is thicker than water» M. Stelmakh and take consideration of his interpretation of school textbooks in 1960–1990 years. Determined the relationship of social and artistic ideals out lined era. Based on the analysis of the novel «Blood of Man – is thicker than water» and the works of contemporary literature reveals a combination of the positive features of the Ukrainian mentality heroes and communist principles. Established relation ship with David Svyryda Miroshnichenko rope from the novel «Weed» Alexander Golovko. It is noted that the characters in the book (Daniel Nechuyviter, Svyryd Smith) is a personification of the movement Ukrainian national communists whose main purpose was to protect the interests of the Ukrainian people who was mental guidelines (anteyizm, Sofiynist, cordocentrism) and Communist assurance was defined. The attention to the tragedy of Ukrainian patriots who, overcoming extremely difficult test for the suffering of others.